Dahsyatul Maut Fī Syi’r ‘Ḥub’ Li Adūnīs - Husnul Hamidah (LISANUDHAD: JURNAL BAHASA, PEMBELAJARAN DAN SASTRA ARAB, 2018)
AbstractAhmed Said Asbar (Adonis) was one of the Syrian poets who invented the world's free poetry Arabic literature. Hubb from the Adonis Library on the theme "First Poems" in the section "Songs to Death" contains simple words and rich meaning and romantic words. the poet pictures love at the first and then sealed with the question of death. The researcher found that finding the meaning in this poetry needs the appropriate analytical method and the most appropriate for the analysis is the method of the semiotic analysis of Michael Riffatere. In this research, the researcher used a semiotic analysis, which was invented Michael Riffatere In this analysis, there are three steps: (1) reading poetry, heuristic and hermeneutic; (2) defining the subject by finding the matrix, model, and varians; (3) creating a hypogram or comparing the text of Hubb and the other text. The researcher found that after the reading of the poetry the sociological criterion in the Hubb of Adonis was death and astonishment. In order to achieve this criterion, the researcher found that the model used is the last part of the text and the text that became hypogram of Hubb is from one of poems by Mahmud Sami Pasha al-Baroudi.Keywords: Semiotics, Michael Riffatere, Adonis دهشة الموت فى شعر"حب" لأدونيسحسن الحميدةUniversitas Airlanggahusnul.hamidah-2016@fib.unair.ac.idملخصكان على أحمد سعيد أسبر (أدونيس) من أحد الشعراء السورى الّذى ابتكر فى الشعر الحر فى العالم الأدب العربى. شعر "حب" من ديوان أدونيس بموضوع "قصائد أولى" فى باب "أغنيات إلى الموت" يحتوى الألفاظ البسيطة وغنية المعنى و تصوير رومنسية غير مركبة. صور فيه الشاعر عند أول شعره  الحب بالدنيا وما فيها ثمّ اختم بالسؤال عن الموت. رأت الباحثة بأنّ إيجاد المعنى المضمون فى ذالك الشعر يحتاج إلى الطريقة التحليلية المناسبة للشعر و أنسبها لتحليل هذا الشعر هى طريقة التحليل السميوطيقى لمكيال ريفاتير وهو لغوى فرنسى.واستخذمت الباحثة فى هذا البحث تحليلا سميوطيقى الذى بدعه السيد مكيال ريفتير. خطّ فى هذا التحليل ثلاث خطوات تعنى (1) قراءة الشعر هيورستيقى و هرمنتيقى (2) تعيين الموضوع بإيجاد المعيار والطراز والنوعيّات (3) إيجاد حيفوكرام أو التناص بين نصّ شعر "حب" و النص الآخر. ووجدت الباحثة بعد قراءة الشعر هورستيقى و هرمنتيقى بأنّ المعيار السميوطيقى فى شعر "حب" لأدونيس هو الموت و دهشة أمره, ولتحقيق هذا المعيار الموجود فى ذالك الشعر وجدت الباحثة بأنّ الطراز المستخذم هى جملة " ماذا يفعل الحب إذا متّ؟". والنص الذى صار حيفوكرام لشعر "حب" لأدونيس من أحد الأشعار لمحمودسامى باشا البارودى وهو شعر "لاتحسبنّ".الكلمات الرئيسية : السميوطيق, مكيال ريفاتير, أدونيس